Scruton and human rights as a Secular Religion. (Cultura Económica, 2025)
This article critiques the transformation of human rights, following the line of thought of Roger Scruton, who sees them today as a kind of “secular religion” that has lost its foundations in natural law. What were originally negative safeguards against state power have become demands for positive —and often contradictory— actions that, instead of limiting the state, end up reinforcing it. Scruton’s analysis is complemented by the discussions of Edward Feser on the need for a metaphysical grounding, John Finnis on the basic goods necessary for human flourishing, and Hannah Arendt, for whom the true issue is ensuring the “right to have rights” within a political community. The text concludes by proposing new paths to recover authority and social cohesion in the human rights discourse.
Keywords: Roger Scruton; human rights; international law; John Finnis; Hannah Arendt